Making more of games: Cultivating perspective-taking through game design. (April 2020) - Dishon, Gideon; Kafai, Yasmin B.
Abstract: Perspective-taking – the consideration of others' mental states and subjective experiences – has been acknowledged as a vital component of interpersonal interactions and communication across divergent social groups. Yet, perspective-taking is neither simple nor automatic; it requires motivation and practice. Though still a nascent area of research, video games have been presented as means of engaging students in perspective-taking due to their immersive and interactive nature. We offer to expand this view and examine the relevance of game design to perspective-taking. Introducing a multiple-case exploratory case study of two groups' work in a game design workshop conducted with high school freshmen, we examine three facets of game design that position this practice as a potentially fruitful context for cultivating perspective-taking: (i) game design is other-oriented – games are created with the intent of being used by others – and hence could elicit motivation to analyze one's work from the perspective of future players; (ii) games are an interactive activity that can be pursued over short periods of time, in public, allowing designers to receive immediate feedback via playtesting sessions; (iii) as game design entails translating abstract insights concerning users' experiences to concrete design decisions, games can function as "objects-to-think-with" in the case of perspective-taking. Highlights: Merely designing a game does not imply that designers will consider players' perspectives. Playtesting motivated and facilitated perspective-taking. Engagement in perspective-taking depended on how "failures" in playtesting were framed. Advanced levels of perspective-taking required instructors to scaffold reflections concerning players' perspectives. Games could potentially function as objects-to-think-with, supporting complex levels of perspective-taking.